2001
DOI: 10.1089/107662901750152864
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Betalactam Therapy for Community-Acquired Pneumonia in the Era of Drug-ResistantStreptococcus pneumoniae:A Randomized Study of Amoxicillin-Clavulanate and Ceftriaxone

Abstract: Empirical antibiotic therapy of community-acquired pneumonia (CAP) has been complicated by the worldwide emergence of penicillin resistance among Streptococcus pneumoniae. The impact of this resistance on the outcome of patients hospitalized for CAP, empirically treated with betalactams, has not been evaluated in a randomized study. We conducted a prospective, randomized trial to assess the efficacy of amoxicillin-clavulanate (2 g/200 mg/8 hr) and ceftriaxone (1 g/24 hr) in a cohort of patients hospitalized fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 33 publications
1
18
0
3
Order By: Relevance
“…There are no studies to date for CAP in Europe that indicate the frequency of isolates with an MIC of ¢4 mg?mL -1 , which is what the prescriber would want to know most [82]. A recent prospective treatment study from Barcelona found that only 10 of 116 (9%) adults admitted to hospital with pneumococcal pneumonia had pneumococci with an MIC of ¢2 [83]. Outcome was the same in the co-amoxiclav treated group as in the ceftriaxone treated group.…”
Section: Antibiotic Resistancementioning
confidence: 98%
“…There are no studies to date for CAP in Europe that indicate the frequency of isolates with an MIC of ¢4 mg?mL -1 , which is what the prescriber would want to know most [82]. A recent prospective treatment study from Barcelona found that only 10 of 116 (9%) adults admitted to hospital with pneumococcal pneumonia had pneumococci with an MIC of ¢2 [83]. Outcome was the same in the co-amoxiclav treated group as in the ceftriaxone treated group.…”
Section: Antibiotic Resistancementioning
confidence: 98%
“…Ancak oluşan infl amatuar yanıt düzeyinin düşük olması ve BDG'ın antioksidan özellikleri, doku hasarının bir göstergesi olan DNA oksidasyonunun diğer tedavi gruplarına benzer çıkmasına neden olmuştur. Mikrobiyolojik analizlerde, seftriakson ve BDG+seftriakson grubunun akciğerlerinde bakteri yükünün az olması, seftriaksonun S.pneumoniae üzerine direkt antimikrobiyal özelliğinden kaynaklanmaktadır 25,26 . BDG grubunda bakteriyemi varlığının sepsis grubuna göre düşük olması; hem IgM'ye bağlı mekanizmalara, hem de daha önceki çalışmalarda 27 bulunan BDG'ın lektine bağımlı ve alternatif kompleman yollarını aktive edici mekanizmalarından kaynaklanmış olabilir.…”
Section: Discussionunclassified
“…One RCT compared penicillin (intravenous [iv] co-amoxiclav [amoxicillin-clavulanic acid] followed by oral co-amoxiclav) versus cephalosporins (iv ceftriaxone followed by intramuscular [im] ceftriaxone). [18] -…”
Section: Penicillin Versus Cephalosporinsmentioning
confidence: 99%
“…Clinical cure , long-term followup (not specified) 136/184 (73.9%) with intravenous (iv) co-amoxiclav (amoxi-378 people [18] RCT cillin-clavulanic acid) followed by oral co-amoxiclav) 144/194 (74.2%) with iv ceftriaxone followed by intramuscular (im) ceftriaxone …”
Section: Clinical Curementioning
confidence: 99%
See 1 more Smart Citation